Disfungsi Asas Kecermatan dalam Kebijakan Penetapan Tanah Terlantar di Indonesia - Robbani, Anila; Subekti, Rahayu; Jaelani, Abdul Kadir (Jurnal Discretie, 2024)
This study aims to find out whether the rule of urgency has been applied in the arrangement of land for sale and forms of legal protection for land holders whose land is designated as land for use. This research uses normative legal research. This research uses case, legal, and conceptual approaches. The results of this study, firstly, the basis of urgency has not been applied in the determination of land for sale originating from HGB based on the analysis of the court ruling related to the BPN decision appeal on land settlement for sale in this study. This is due to three factors, namely the substance of the law, the legal structure, and the legal culture. Second, the form of legal protection for HGB Holders whose land is established as land transfer based on the theory of the legal protection of J.B. J. B. ten Berge, there are three forms of protection namely protection through democracy, protection through hierarchical relations of government, and protection through jurisdictional arrangements. Of the three types of protection of such law, according to the analysis of the Author, the protection through the legal arrangement has been optimally applied as legal protection to the HGB Holder.